EVALUATION OF PLANT EXTRACTS AGAINST LUNG CANCER USING H460 CELL LINE - G, TRIPATHY; D, PRADHAN; S, PRADHAN; T, DASMOHAPATRA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Mammalian tumor cells show imperviousness to chemotherapy and its serious symptoms lessens the clinical adequacy of an extensive assortment of anticancer drugs. Plant-derived compounds show numerous valuable impacts and can restrain a few phases of malignancy of cancer. Despite there is paramount progress in cancer therapeutics in the last decades, the need to find, grow new and synergistic plant predicated anticancer specialists are in the developing stage. In the present study, we endeavored to exploit bioactive compounds of two plants viz. Limonia acidissima and Syzygium cumini, investigated their antiproliferative properties for lung cancer and evaluated the haemolytic activity. Methanol extracts of these plants were experimented for cytotoxic activity and found that L.acidissima and S.cumini selectively inhibited H 460 cell proliferation and found that the two plants are non-haemolytic. Our study deduce that the potential bioactive compounds of these plants have vibrant chance to fight lung cancer as were seen to be non-haemolytic to blood cells and they are very much recorded as a traditional medicine for various therapeutic uses.